RELEVANSI METODE PENDIDIKAN DALAM HADIS TARBAWI TERHADAP PRAKTIK PENDIDIKAN KONTEMPORER - Ahmad Fatoni; Azet Sampurna; Bagas Armayoga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The tarbawi hadiths are a collection of teachings of the Prophet Muhammad that are directly related to the principles and methods of education. This study aims to analyze the relevance of educational methods in tarbawi hadith to contemporary educational practices. The methods of uswah (exemplary), targhib-tarhib (motivation and warning), and hiwar (discussion) are the main pedagogical approaches explored in this study. This research uses a library research method with a qualitative approach and thematic analysis. Data were obtained from various scientific literatures that discuss tarbawi traditions as well as major hadith sources such as Sahih Bukhari and Sahih Muslim. The results of the study show that the three methods have a strong alignment with the principles of modern education such as active learning, character education, and the role of the teacher as a role model. Thematic analysis of the tarbawi traditions reveals that the Prophet's method is highly adaptive, communicative, and forms the foundation of value-based learning. However, the integration of this method in the current educational context is faced with internal challenges, such as the lack of educators' understanding of tarbawi hadith, as well as external challenges in the form of the influence of globalization and digital technology. On the other hand, opportunities for integration remain open through strengthening the curriculum, training teachers, and utilizing technology as an educational tool. With the right implementation strategy, the Prophet's educational methods can enrich today's educational practices, forming a generation that is intellectually intelligent as well as spiritually and morally strong.